Analisis dan Evaluasi Aplikasi Sistem Pasar Modal Syariah di Indonesia - Siti Murtiyani; Nuhbatul Basyariyah; Hanifah Zahra (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2015)
Islamic Capital Market System in Indonesia is part of the capital market in general, so that the mechanisms, procedures and transactions in the capital market is not much different between the two. Neither the mechanisms stocks, Islamic bonds and other instruments in the Islamic Capital Market System. This study aimed to analyze and evaluate the application of the system of Islamic Capital Market in Indonesia. In this research explains in a descriptive and qualitative content analysis of the implementation of Islamic Capital Market in Indonesia. Data collection techniques used were interviews, observation, and then perform a critical analysis of the implementation of the system application of Islamic Capital Market in Indonesia. The results showed that the application of the system of Islamic Capital Market in Indonesia has not been reflected as Islamic Capital Market System in Islamic Economic System, both in terms of the shape of the company is a Limited Liability Company, from the mechanism of transactions and products in Islamic Capital Markets. Therefore, Islamic Economics providing solutions for the implementation of Islamic Capital Market System that right, so that it can be realized Maqasid Al-Sharia in the State Indonesia.